Optimalisasi Mutu Pendidikan Islam Melalui Strategi Komunikasi Organisasi Dalam Bingkai Kepemimpinan dan Perilaku Kerja yang Inklusif - Muslimin, Ikhwanul (AKSI: Jurnal Manajemen Pendidikan Islam, 2023)
This article discusses organizational communication strategies in improving the quality of Islamic education. Concepts and theories of organizational communication, including organizational communication models, communication in organizations, and the role of leadership in communication have been explained as a basis for understanding communication strategies. The approach used in this research is qualitative with a literature study method, researchers use several books, journals, and the results of recent observations as references. The findings reveal that a good communication strategy begins with determining goals and objectives in accordance with the vision of Islamic education institutions. Understanding the audience, such as students, lecturers, and staff, is key in delivering relevant messages. The use of appropriate communication channels, sensitive crisis and conflict management, continuous evaluation and feedback, as well as the involvement of the entire educational community, are important elements in achieving optimal educational quality. This article proves that effective communication is the key to achieving an optimal and relevant quality of Islamic education in facing the challenges of the times.